Hypertensive Emergency in Aortic Dissection and Thoracic Aortic Aneurysm-A Review of Management - Himani Gupta; Prateek K. Gupta; Ali Khoynezhad (MDPI AG, 2009)
Over the last few decades, treatment for aortic dissection and thoracic aortic aneurysms has evolved significantly with improvement in outcomes. Treatment paradigms include medical, endovascular and surgical options. As aortic dissection presents as a hypertensive emergency, diligent control of BP is of utmost importance in order to reduce the progression of dissection with possible aortic branch malperfusion. Treatment should begin on arrival to the emergency department and continues in the intensive care unit, endovascular suite or the operating room. Novel antihypertensive medications with improved pharmacological profile and improved surgical techniques, have improved the prognosis of patients with aortic aneurysm and/or aortic dissection. Nevertheless, morbidity and mortality remain high and hypertensive emergency poses a significant challenge in aortic dissection and thoracic aortic aneurysms.